The Craftsmen Society and the Worker Education in Costa Rica in end of the 19th Century - Angulo Brenes, Sonia (2022)
This article has two objectives. First, it exposes the appearance of the Craftsmen Society (1874) as one of the first craftsmen organizations in Costa Rica that it allowed the worker merger and solidarity, and second, it recovers the worker instruction projects that such association had. The analysis is based on the historical recovery of the organization from the treatment of the El Artesano newspaper mainly, its official publishing medium. It was analyzed a total of fifty copies. It concluded that the Craftsmen Society was constituted in a fundamental base to understand the first trace of the worker craftsmen organization configuration in the country and their cultural and educational objectives especially due to the education projects made in 1889, which they strongly influenced the worker culture.